DESCRIPTION OF TUBERCULOSIS PATIENTS AT SANGGONA HEALTH CENTRE, ULUIWOI SUB- DISTRICT, EAST KOLAKA DISTRICT IN 2023 - Chandra, Chandra; Tosepu, Ramadhan (Preventif Journal, 2024)
ABSTRACT Tuberculosis is one of the deadliest infectious diseases in the world. seen from the trend of cases in Sanggona Health Centre, from the past 3 years that, there is an increase in TB cases in the Sanggona Health Centre working area. The number of cases in 2021 was 10 active cases, and in 2022 there were 9 active cases, in 2023 there was an increase in cases again with a total of 10 active cases. This research is descriptive quantitative which aims to describe tuberculosis patients in Sanggona Health Centre Sub-District Uluiwoi East Kolaka District in 2023 supported by Primary data from Respondents and secondary data from Puskesmas Sanggona. The results of this study indicate that the age group that ranges affected by pulmonary tuberculosis is the productive age between 15 - 64 years, totalling 11 people with male gender 6 people, a total of 11 respondents with 6 people working as farmers and 11 people with income < 1,500,000, for the education level there are 6 people with high school education, for behaviour obtained with the results of 6 active smokers. Availability of drugs in health facilities 11 respondents with information available, accessibility to health facilities 3 respondents are quite easy, and 8 respondents are difficult due to distance and damaged roads. It is hoped that all elements of health starting from the East Kolaka District Health Office, Fasyankes, and the community need self-awareness in maintaining environmental health and personal health to avoid pulmonary TB infectious diseases. Keywords: Sanggona Health Centre, Tuberculosis